DIFFERENCE OF COPING STRATEGIES BETWEEN EARLY ADOLESCENT MALES AND FEMALES - Fatmawati, Fatmawati; Almigo, Nuszep; maryam, siti; Gani, Fadhli A (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2016)
Background: A number of studies argued that women and men have differences in both quantity and quality of psychosocial health problems, and women are more prone to depression (Compas, Orosan, & Grant, 1993). This latter may be explained by the gender differences of the ways of coping (Nolen-Hoeksema, 1991).Objective: To determine the differences of coping strategies between early adolescents male and female. Methods: Independent Sample T-Test was operated to examine the difference of coping strategies between early adolescents male and female. Instrument: Coping strategies were assessed using the newly developed Self-Report Coping Scale (SRCS, Causey & Dubow, 1992). Results: Results indicated a non-significant trend in approach coping strategy for early adolescent females (M = 48.20, SD = 6.48) over early adolescent males (M = 45.00, SD = 8.78), t(79) = -1.88, p = .06. On the other hand, there was a significant effect for gender in avoidance coping strategy, t(79) = -2.40, p = .02, with early adolescent females receiving a higher score than early adolescent males. Conclusion: The findings supported the previous evidence that the coping strategy between early adolescents male and female was differ.